Capacity assessment and spatial analysis of cervical cancer services in The Gambia - Meghan E. Mali; Ousman Sanyang; Katherine L. Harris; Justin Sorensen; Mustapha Bittaye; Jonathan Nellermoe; Raymond R. Price; Edward K. Sutherland (BMC, 2023)
Abstract Background Cervical cancer is the most common cancer and the leading cause of cancer-related death in Gambian women. The Gambian Ministry of Health is striving to improve access to screening, diagnostic, and treatment services for cervical cancer, but comprehensive data on currently available services is limited making it challenging to appropriately prioritize the ideal next steps for expanding care. This study aims to describe the current services available for the prevention, screening, and treatment of cervical cancer in The Gambia and provide suggestions for expanding geographic access to care. Methods A survey aimed at assessing the availability of key cervical cancer-related services was developed and then administered in person by research assistants to all secondary and tertiary health facilities (HFs) in The Gambia. ArcGIS Pro Software and 2020 LandScan population density raster were used to visualize and quantify geographic access to care. Survey results were compared with published targets outlined by the Gambian Ministry of Health in the "Strategic Plan for the Prevention and Control of Cervical Cancer in The Gambia: 2016-2020." Results One hundred and two HFs were surveyed including 12 hospitals, 3 major health centers, 56 minor health centers, and 31 medical centers/clinics. Seventy-eight of these HFs provided some form of cervical cancer-related service. HPV vaccination was available in all health regions. Two-thirds of the population lived within 10 km of a HF that offered screening for cervical cancer and half lived within 10 km of a HF that offered treatment for precancerous lesions. Ten HFs offered hysterectomy, but nine were located in the same region. Two HFs offered limited chemotherapy. Radiotherapy was not available. If all major health centers and hospitals started offering visual inspection with acetic acid and cryotherapy, 86.1% of the population would live within 25 km of a HF with both services. Conclusions Geographic access to cervical cancer screening, and precancer treatment is relatively widespread across The Gambia, but targeted expansion in line with the country's "Strategic Plan" would improve access for central and eastern Gambia. The availability of treatment services for invasive cancer is limited, and establishing radiotherapy in the country should continue to be prioritized.